Managing Client and Contractor’s Relationship in Multi-National Project Site to Forestall Delayed Project Abandonment. Case Study: OLKILUOTO 3 - Adefolalu, Olufemi (My University, 2018)
The construction of Olkiluoto 3 Nuclear Power Plant is undoubtedly a mega project based on its magnitude and several players, different activities, profession , responsibility all coming together resulting in the ultimate goal of producing safely working nuclear power plant. This is a unique mega project taking a longer period to complete and multi-national that at one time has up to 4000 workers from 55 countries with over 1700 subcontractors from over 27 countries and managing such a project is not as easy as embarking on a journey from point A to point B, because there were challenges that by error of omission were over looked and hence resulted into decade of delays and near abandonment. Additionally, there were disputes between the client and the contractor and expectedly public debates about action and inaction of parties involved . Commendably, the project wheel was kept running , the disputes are being managed, project issues were are gradually resolved and new challenges are being managed as they evolved. The journey so far and how the client’s and contractor’s relationship have been managed enumerates lessons for effective project and quality management practices.
Keywords: client; contractor; quality planning; Olkiluoto 3 nuclear power plant; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|